Gaya Hidup Konsumtif dalam Perspektif Teori Kepribadian Carl R. Rogers dan Refleksi Kritis bagi Pembentukan Karakter Bangsa - Annas Fitria Sa'adah (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2023)
The consumptive lifestyle can be a form of individual actualization by owning the goods they want. This lifestyle can then influence the dynamics of individual self formation, which in Carl R. Rogers' theory is called self-concept. The purpose of this research is to know the basis of human existence in a consumptive lifestyle and to analyze self-concept in a consumptive lifestyle based on Carl R. Rogers' personality theory. This research method is library research (library research study). The data sources used include all books by Carl. Rogers or others' work on him and other literature relevant to the research topic. Data analysis was carried out through three stages, namely hermeneutics, holistic and heuristics. From the results of data analysis it was found that the basis of human existence for a consumptive lifestyle is freedom. Carl R. Rogers views humans as forms of his self-concept and his experience and interpretation of the environment that surrounds him. The consumptive lifestyle can be an individual self-ideal that is actualized through the ownership of goods. This is motivated by the fact that basically human behavior is goal-directed, namely to satisfy needs as they experience them. The results of this study provide an overview of the philosophical dynamics of the phenomenon and the existence of consumptive individuals. In addition, it is hoped that it can become a reference in developing the ability to think and act in response to consumptive behavior, especially in carrying out national character.